FORMULASI SEDIAAN MASKER GEL Peel-off EKSTRAK DAUN KECOMBRANG (Etlingera elatior) SEBAGAI PERAWATAN PADA KULIT WAJAH - sembiring, bunga mari (Jurnal Penelitian Farmasi & Herbal, 2021)
Kecombrang (Etlingera elatior) leaves contain flavonoid compounds, saponins, alkoloid, and tannins. Based on the compounds owned kecombrang leaves can be used as a peel off gel mask. The purpose of this study was to make a peel off gel mask formulation of kecombrang (Etlingera elatior) leaf extract as a treatment for facial skin. The gel peel off mask formulation was made with 4 formulations, F0 = 0%, FI = 10%, FII = 15%, FIII = 20%. Extraction method is done using maceration method with 96% ethanol solvent. Evaluation of peel off gel mask preparations, including organoleptic tests (color, odor, shape), pH measurement of preparations, homogeneity test, dry time test, spreadability test. Peel off gel mask preparations that have effectiveness as treatments for facial skin are FIII formulations with a concentration of 15% that meet the evaluation test requirements, and positive control (Naturgo) which has had better effectiveness test results. The results of the evaluation test of peel off gel mask preparation, including organoleptic test (color, odor, shape), pH measurement of the preparation, homogeneity test, dry time test, dispersion test according to the gel preparation parameters.